Pantyon ilang pamahiin, tradisyon, at kuwento ng paglilibing sa Kabite. - Lubang, Jeffrey Alfaro; Cavite Studies Center (Manila Ige Ramos Design Studio, 2007)
Tradition of funeral rites and ceremonies for the dead of local people in Cavite Province.
"Proyekto ng Cavite Studies Center, De La Salle University-Dasmariñas."
Includes musical score with staff notation.
Keywords: Funeral rites and ceremonies -- Philippines -- Cavite Province; Burial -- Philippines -- Cavite Province